Pengembangan Desain Instruksional Pendidikan Agama Islam - nuroyn syafiun (LP3M KH Yazid Karimullah Institute, 2024)
Abstract: This study aims to analyze the implementation of the model for developing Islamic Religious Education learning designs in schools. This study used a development research design by Walter Dick & Lou Carey with 9 steps for developing a learning design: (1) Identifying teaching objectives; (2) Performing instructional analysis; (3) Identify students' initial behavior/characteristics; (4) Formulate performance objectives; (5) Development of benchmark reference tests; (6) Development of teaching strategies; (7) Development or choosing to teach; (8) Design and carry out formative evaluations; And (9) Teaching revision. The results of the study show that the development of learning designs requires the achievement of 21st century competencies such as critical thinking, creativity, communication, and collaboration. Based on these demands, the development of Islamic Religious Education learning must be based on multimedia.